A murine Skint6 W168X allele contributes to autoimmune disease in a transgenic model. (March 2022) - Ju, Jiyu; Wang, Hui; Lian, Meng; Bao, Yatao; Zhang, Yanyan; Xu, Zhiwei
Background: The genetic factor is a great driver of systemic lupus erythematosus. A Skint6 W168X allele was previously identified in the murine lupus susceptibility rec1d1 sublocus. The purpose of this study is to investigate the pathogenic role and mechanism of the Skint6 W168X allele in lupus autoimmune disease. Methods: The gene-editing CRISPR/Cas9 system was used to generate transgenic models with the Skint6 W168X allele. PCR and Sanger's sequencing techniques were applied to mRNA quantification and DNA sequence detection. Flow cytometry was adopted for immunophenotyping. Pathological evaluation of kidneys and lungs was performed using several immunopathological approaches. Results: The transgenic models with the Skint6 W168X allele were created, including B6.Skint6 X/X and B6.lpr.Skint6 X/X strains. The B6.lpr.Skint6 X/X mice showed bigger spleen and lymph nodes, more lymphocytes and effector T cell populations, more severe nephritis with more IgG and C3 deposit in glomeruli as well as worse proteinuria, and more severe lung inflammation than control B6.lpr mice. In addition, a skint6 receptor binding Skint6 peptide was identified from T and B lymphocytes. B6.Skint6 X/X mice have lower percentages of skint6 receptor + T and B cells in spleen than B6 mice. Conclusion: The Skint6 W168X allele in murine lupus rec1d1 sublocus was validated to be a pathogenic mutant gene and contributes to autoimmune disease through producing a truncated Skint6 peptide of binding the skint6 receptors on lymphocytes.